Epidemiology of COVID-19 in Africa - daily cumulative index and mortality rate - David, Kenneth Bitrus; Thomas, Naomi; Solomon, Joan Kuyet (International Journal of Infection Control, 2020)
COVID-19 outbreak which originated from Wuhan, a city in China has spread to over 180 countries in the world, disrupting several sectors of the human life, and causing deaths. This unprecedented event has affected 55 countries in Africa in different ways. This study aims to outline the current epidemiological data of COVID-19 in Africa. The number of confirmed cases and deaths in Africa was obtained from COVID-19 Dashboard by the Center for Systems Science and Engineering (CSSE) at Johns Hopkins University. Mortality rate and daily cumulative index were calculated for each country. The mortality rate in Africa is low compared to other Continents regardless of the high Daily Cumulative Index recorded.